Modelagem matemática da interação populacional entre Diatraea saccharalis (Fabricius, 1794) e o parasitoide Cotesia flavipes (Cameron, 1891) - Rodero, Donavan Peres (2016)
The sugarcane borer, Diatraea saccharalis, is one of the major pests in Brazil causing great damage to the crop. Studies estimate that, for each 1% of sugarcane borer infestation, the yield losses will be 1.14%, the reduction in sugar content and ethanol production 0.42% and 0.21%, respectively. Thus, for Brazil meet the growing demand for sugar and ethanol is of paramount importance to enhance the management programs of this pest. For this, new techniques and tools such as mathematical modeling arise to assist producers. The present study aims to describe the interaction between population Diatraea saccharalis and one of its natural enemies, the parasitoid Cotesia flavipes, through mathematical modeling and computer simulation. The Biology and interaction between the two insects were characterized by literature, allowing the development of the model of the predator-prey differential equations (Lotka-Volterra), which was validated by computer simulation. The equilibrium situations and scenarios were influenced by the model coefficients, as well as the variables considered in computer simulation altered the dynamics of interaction, indicating the importance of adjustment for variables for the particular producer's situation. This study allowed a greater knowledge of the interaction between population D. saccharalis and C. flavipes, contributing by simulating scenarios for the definition of pest control strategies in the sugarcane fields.